Teriparatide for the rapid resolution of delayed healing of atypical fractures associated with long-term bisphosphonate use - Mastaglia, Silvina Rosana (2016)
Bisphosphonates (BPs) are the most widely used drugs to treat osteoporosis. However, recent reports associated to long-term BPs use with atypical low-impact fractures and prodromal pain. It is estimated that 26% of the cases of atypical fractures associated with the long-term use of BPs show delayed healing or nonunion. Teriparatide [PTH1-34] (TPTD) is an anabolic drug shown to be effective in stimulating bone formation. The aim was to describe the course of a right diaphyseal femoral fracture sustained by a patient on long-term BPs treatment. A 57-year-old postmenopausal Caucasian female presented with delayed healing of a right femoral diaphyseal fracture 10 months after the fracture, despite having received orthopedic treatment. The fracture was preceded by progressive, severe, and bilateral thigh pain. Her medical history included osteopenia that was treated with alendronate over 7 years. On presentation at our clinic, the patient ambulated with the aid of a walking cane. The diagnosis was an atypical right femoral fracture associated with long-term alendronate use. The levels of the following parameters were measured: mineral metabolism laboratory: intact parathormone, 40 ng/mL (reference values (rv): 10–65 ng/mL); 25-hydroxyvitamin D, 40 ng/mL (rv: >30 ng/mL); serum Crosslaps, 318 ng/mL (rv: 80–590 ng/mL); and bone-specific alkaline phosphatase, 76UI/L (rv: 31–95UI/L)]. Magnetic resonance imaging of the left femur was performed, which revealed a diaphyseal stress fracture. She was prescribed 20 μg/day of subcutaneous (s.c.) TPTD (PTH1-34, Forteo; Eli Lilly Co., Indianapolis, IN, United States). A computed tomography scan performed 3 months later showed that the fracture had healed; the patient was able to resume her usual activities. Twenty micrograms per day of s.c. TPD accelerated the healing of the atypical fracture associated with long-term alendronate therapy, allowing a fast recovery of ambulation and quality of life.